Gaps between General and Special Education Policies and their Implications Regarding Inclusive Education in Pakistan: A Qualitative Study - Afshan Khalid; Dr. Hina Fazil; Arooj Amanat; Uswa Rasool; Hamayoun Shah Nawaz; Dr. Muhammad Nadeem Iqbal (Al-Qanṭara, 2023)
Education is considered the most significant aspect of the social and economic development of any country. Regions are still far from properly adopting the notion of inclusive education as altering the education system at large and struggling for establishing an inclusive setup despite discrimination. The main purpose of the study was two-fold. First, review the literature to investigate the special and general educational policies regarding the formulation and implementation of inclusive education in Pakistan. The second purpose was to identify the gaps between the policies regarding inclusive education. The researchers used a qualitative research approach and multiple case studies as research designs to explore the phenomena. A content analysis technique was employed to review the literature. For this purpose, researchers over-viewed 17 research studies in the field of inclusion of persons with disabilities. To find out the gaps between these policies a semi-structured interview was conducted. In this connection, seven participants were purposively selected including, one deputy director of planning; one director academic; two district education officers from the special education department; one head of special education school; two heads from the general education department. The obtained data through semi-structured interviews were analyzed with the thematic analysis technique. The results of the study reported that in different eras policies for inclusive education have been formulated but could not be implemented appropriately. The content analysis revealed that in Pakistan inclusive education is an emerging trend and is gaining momentum but slowly. A lot of work and reforms have to evolve for implementation of the inclusive education in Pakistan. Keywords: general and special education policies, inclusive education, multiple case studies